Cinema e revolução as produções cinematográficas anarquistas na revolução espanhola - Vieira, Gustavo Pierzchalski (2020)
The links between cinema and anarchy began in Europe at the beginning of the 20th century; this approach was established through documentary films with revolutionary and educational themes. During the Revolution in Spain between 1936 and 1939, Spanish anarchists made the art of cinema a form of resistance and propagation of the anarchist ideology. With the predominance of anarcho-unionist practice in Spain, anarchists produced films, reportages and documentaries based on the collectivization of the media that involved the entertainment industry. This form of production took place as a result of the changes that occurred in society as a result of the Revolution, allowing the entertainment unions to assume ownership of the movie theaters and shows, in addition to directing the movie studios. The anarchists provided a new type of cinema in Spain, a cinema capable of replacing a national production that operated based on a capitalist market system. The Spanish anarchist cinema was able to transform the film industry into something new and inventive that successfully manifested the most diverse libertárian experimentation that marked the short period of the revolution, which dwells in the life and imagination of those who fought for freedom and the transformation of society